Industrial exoskeletons from bench to field: Human-machine interface and user experience in occupational settings and tasks - Baldassarre, Antonio; Lulli, Lucrezia Ginevra; Cavallo, Filippo; Fiorini, Laura; Mariniello, Antonella; Mucci, Nicola; Arcangeli, Giulio (Frontiers in Public Health, 2022)
Objective. Work-related musculoskeletal diseases (WRMSDs) are considered nowadays the most serious issue in the Occupational Health and Safety field and industrial exoskeletons appear to be a new approach to addressing this medical burden. A systematic review has been carried out to analyze the real-life data of the application of exoskeletons in work settings considering the subjective responses of workers. Methods. The review was registered on PROSPERO. The literature search and its report have been performed following the PRISMA guidelines. A comprehensive literature search was performed in PubMed, EMBASE, Web of Science and Scopus. Results. 24 original studies were included in the literature review. 42% of the papers retrieved included automobilist industry workers, 17% of the studies evaluated the use of exoskeletons in logistic facilities, 17% articles involved healthcare. The remaining 6 papers recruited farmers, plasterers, wasting collectors, construction workers and other workmen. All the papers selected tested the use of passive exoskeletons, supporting upper arms or back. Usability, perceived comfort, perceived exertion and fatigue, acceptability and intention to use, occupational safety and health and job performance and productivity were the main topic analyzed. Conclusion. Exoskeletons are not a fix-all technology, neither for workers nor for job tasks; they tend to show more their potential in static activities while in dynamic tasks they can obstacle the regular job performance. Comfort and easiness of use are the key factor influencing the user’s experience. More research is needed to determine the most effective and safe ways to implement exoskeleton use in occupational settings.